The Psalms as Christian worship : a historical commentary - Waltke, Bruce K.; Houston, J. M. (James Macintosh), 1922-; Moore, Erika (Grand Rapids, Mich. : William B. Eerdmans Pub. Co., 2010)
This collaboration by two esteemed evangelical scholars blends a verse-by-verse exposition of select psalms with a history of their interpretation in the church from the time of the apostles to the present. Bruce Waltke, who has been teaching and preaching the book of Psalms for over fifty years, skillfully establishes the meaning of the Hebrew text through the careful exegesis for which he is well known. James Houston traces the church's historical interpretation and use of these psalms, highlighting their deep spiritual significance to Christians through the ages. Waltke and Houston focus their in-depth commentary on thirteen psalms that represent various genres and perspectives or hold special significance for Christian faith and the life of the church, including Psalm 1, Psalm 23, Psalm 51, and Psalm 139. While much modern scholarship has tended to "despiritualize" the Psalms, Waltke and Houston's "sacred hermeneutic" listens closely to the two voices of the Holy Spirit heard infallibly in Scripture and edifyingly in the church's response. A masterly historical-devotional commentary, The Psalms as Christian Worship will deepen the church's worship and enrich the faith and life of contemporary Christians. - Publisher.
A survey of Second Temple period interpretation of the Psalms -- Historical introduction to the interpretation of the Psalms in church orthodoxy -- History of interpretation since the Reformation : "accredited exegesis" -- Psalm 1 : the rewarded life -- Psalm 2 : ask of me, my son -- Psalm 3 : living in the borderland : morning prayer after a dark night -- Psalm 4 : an evening prayer in crisis -- Psalm 8 : I AM rules through "infants" -- Psalm 15 : a liturgical decalogue -- Psalm 16 : my body will not decay -- Psalm 19 : a royal sage praises and petitions I AM -- Psalm 22 : prophetic psalm of Christ's Passion -- Psalm 23 : the good shepherd -- Psalm 51 : "the psalm of all psalms" in penitential devotion -- Psalm 110 : "sit at my right hand" -- Psalm 139 : search me, God.
Includes bibliographical references and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Bible; Criticism, interpretation, etc